Analysis of medicine advertisement produced in Brazil. - Wzorek LF; Correr CJ; Trindade ACB; Pontarolo R (Centro de Investigaciones y Publicaciones Farmaceuticas, 2007)
Objective: To analyze the compliance of drug advertisements with regulations in Brazil, subject to Resolution RDC No. 102/2000 since 2000, which abides by the WHO's (World Health Organization) Ethical Criteria for Medicinal Drug Promotion, published in 1988. Methods: Drug advertisements running within the period of October 2002 to October 2003 were collected and recorded. Media sources included various AM and FM radio stations, television channels, newspapers, and magazines, as well as printed material distributed in doctors' offices, hospitals, drugstores, conferences, billboards, and bus doors. All sources were located in Curitiba City, Brazil, and its surrounding area. Advertisement content was analyzed according to a conformity checklist prepared based on the legal requirements of RDC No. 102/00. Results: A total of 827 advertisements for 517 different products, 83.91% regularly registered as medicinal drugs and 16.09% unregistered products that should be registered according to the Brazilian regulations, were recorded and collected. Approximately 74.73% of the advertisements did not comply with regulations; on average, such advertisements had 4.6 infractions each. Conclusions: The results of this research suggest that RDC No. 102/00 is not followed, which strengthens the need to adopt new forms of regulation to prohibit excesses of the pharmaceutical industry and to protect the population from abusive and misleading drug advertising.